Technical Note: An open source solution for improving TG‐263 compliance. Issue 9 (19th September 2019) - Cardan, Rex A.; Covington, Elizabeth L.; Popple, Richard A.
Abstract: Purpose: Compliance with TG‐263 nomenclature standards can be challenging. We introduce an open source solution to this problem and evaluate its impact on compliance within our institution. Materials/methods: The TG‐236 nomenclature standards were implemented in our clinic in two phases. In phase 1, we deployed TG‐263 compliant templates for each disease site. In phase 2, we developed and deployed a script for evaluating compliance which presented errors to the user. After each phase the compliance was recorded. Results: Mean compliance errors prior to phase 1 was 31.8% ± 17.4%. Error rates dropped to 8.1% ± 12.2% across phase 1 and dropped further to 2.2% ± 6.9% during the automation system deployed in phase 2. Conclusion: Both structure templates and automation scripts are very useful for increasing compliance with structure naming standards. Our software solution is made available on GitHub for other institutions to implement.